Biohydrometallurgy in the recovery of metal values. - Rosales Urbano, Victor (2001)
In current times, and with regard to extractive metallurgy, the use of new technologies for the recovery os values that can be present in minerals or in their concentrates and which can be hardly extracted by means of conventional technologies are shown special interest. One of these new technologies is bacterial leaching. In the present work, the theoretical aspects of bacterial leaching are made known, remarking on the importance of the mechanism involved in the biooxidation of Fe(II) towards Fe(III). Experimental aspects are also mentioned, such as the methodology followed in biohydrometallurgical processes. To that effect, results of tests carried out in the laboratory are presented, with which we can better outline the interest that the use of biological systems in the recovery of metallic values arouses.